Determine the Biofilm Formed by Using ELISA Technology for Gram-Negative Bacteria Isolated from Wounds and Burns Infections, and the Study of the Production of the Biofilm Molecularly. - Flaih, Omar Nama; Najeb, Laith Musleh; Mohammad, Rana Kadhim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was designed to investigate the capability of gram-negative bacteria that isolated form wound and burn infection to production of Biofilm which included (32) isolates, which have multi – drug resistant to antibiotics. The isolates included (10) Pseudomonas aeruginosa, (9) Klebsiella pneumoniae, (6) Escherichia coli, (5) Proteus mirabilis and (2) Enterobacter cloacae. The method used method links the crystal violet with biofilm and reading by ELISA which was adopted on the values of optical density of violets that linked to the mass of biofilm at the wavelength of (620) nm, the test results showed variation of biofilm composition for all bacterial species depending on the optical density value while the most production of biofilm was product form bacterial isolated from diabetes patients wound. Agarose gal electrophoreses results show that all isolate have a different plasmid profile according to the (size and position), it was also that temperature used as a curing factor causes a high frequency loss the plasmid from all isolates and according to this reason the yield was different after the curing that maybe refers to the role of both plasmid and chromosome in regulating this phenomena.